2009
DOI: 10.1186/cc7161
|View full text |Cite
|
Sign up to set email alerts
|

Should dialysis be offered in all cases of metformin-associated lactic acidosis?

Abstract: Metformin is commonly used in diabetes mellitus type 2, with lactic acidosis being a rare but potentially fatal complication of this therapy. The management of metformin-associated lactic acidosis (MALA) is controversial. Treatment may include supportive care, activated charcoal, bicarbonate infusion, hemodialysis, or continuous venovenous hemofiltration. In the previous issue of Critical Care, Peters and colleagues systematically evaluated outcomes in MALA patients admitted to their intensive care unit. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…We could speculate that the rapid correction of acidosis was not associated with total clearance of metformin from intracellular compartment and toxicity still exerts its effect in endomembrane system and proteins, resulting in late cell death. [21][22][23]. It is still unclear why some patients recover from severe MALA while others invariably die.…”
Section: Discussionmentioning
confidence: 99%
“…We could speculate that the rapid correction of acidosis was not associated with total clearance of metformin from intracellular compartment and toxicity still exerts its effect in endomembrane system and proteins, resulting in late cell death. [21][22][23]. It is still unclear why some patients recover from severe MALA while others invariably die.…”
Section: Discussionmentioning
confidence: 99%
“…Other combined therapeutic modalities were also reported to successfully treat severe cases [3,6,7,16]. Although Peters et al [1] later reported that they had failed to reduce the mortality rate among patients treated with haemodialysis compared with those who did not receive such treatment, Finkel's [20] observation that more severe patients were scheduled for haemodialysis rather than for non-haemodialysis therapy might explain the lack of success of Peters and colleagues. Thus, there are no conclusive data available to indicate which dialysis technique is superior.…”
Section: Discussionmentioning
confidence: 99%
“…Although we felt MALA was unlikely, we could not exclude it. Fortunately, one of the critical interventions beyond supportive care for severe MALA appears to be hemodialysis [61], which we were preparing to do already for potential toxic alcohol poisoning.…”
Section: Could This Be Metformin-associated Lactic Acidosis?mentioning
confidence: 99%